The Relationship between Market Value, Capital Expenditures, Value Creation and Product Market Power - Arash Arianpoor; Saleh Orfizadeh (Iranian Journal of Accounting, Auditing & Finance)
The present study's primary purpose is to investigate the relationship between the company's market value, capital expenditures, value creation, and the product market power of the companies listed on the Tehran Stock Exchange. The study's statistical population consists of 129 companies during 2013-2018. The Combined data method has been used to test the research hypotheses. The Herfindahl–Hirschman, the Lerner, and the Industry-adjusted Lerner Index measure product market power. To measure the company's market value, Maditinos et al. (2011) were used to measure capital expenditures. The model presented in Liao, Lin and Lin, (2016) has been used, and the Pulic Model (2004) to measure value creation. The results show a positive (negative) correlation between the market value of the company and the Herfindahl–Hirschman Index and Lerner Index (Industry-adjusted Lerner Index). There is a positive (negative) correlation between capital expenditure and the Herfindahl–Hirschman index and Lerner Index (Industry-adjusted Lerner Index). The results show a negative (positive) correlation between value creation and the Herfindahl–Hirschman Index (Lerner Index and Industry-adjusted Lerner Index).